Recycling of polyurethane by acidolysis: The effect of reaction conditions on the properties of the recovered polyol. (26th March 2021) - Gama, N.; Godinho, B.; Marques, G.; Silva, R.; Barros-Timmons, A.; Ferreira, A.
Abstract: Recently, a method for the recycling polyurethane (PU), the acidolysis, was reported in which dicarboxylic acids (DA) were used as cleavage agents. Yet, the effect of reaction conditions on the properties of the recovered polyol (RP) was not discussed. Therefore, aiming at achieving in-depth knowledge of acidolysis, in this work, the effect of the recycling conditions on the properties of RP was statistically evaluated. Temperature and PU/DA ratio were found to be the predominant factors with influence of 62.4% and 31.5% on the hydroxyl number (OHnumber ), respectively. In turn, the acid value (AV) proved to be dependent on several factors and their interactions. Yet, the major influence on AV, the combination of PU/DA ratio and temperature, has 39.7% of influence. Using linear regression to predict the properties of the RP, both the experimental and the predicted values presented high correlation. Afterwards, flexible polyurethane foams (PUF) were produced using up to 30% (w/w) of RP as partial substitute of virgin polyol. It was observed that all foams present similar density, although the presence of the RP enhances their stiffness, which was attributed to the higher content of aromatic moieties of RP. Therefore, the suitability of this recycling method and the subsequent use of the reaction products in the production of new foams was demonstrated. This is fully in line with the principles of circular economy. Graphical abstract: Image 1 Highlights: Polyurethane foams were recycled via acidolysis using succinic acid. The effect of the recycling conditions was statistically evaluated. Temperature and polyurethane/dicarboxylic acid ratio are the predominant factors. Polyurethane foams were produced using recovered polyol. The foams are suitable for its use in automotive and domestic applications.